The Concept of Wayfinding As a Criterion of Design: Definitions and Debates - Ercevik Sonmez, Begum; Erinsel Onder, Deniz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
Wayfinding is finding of the way that reaches the particular destination of individuals without any delays or concerns. Although moving from one space to another is a straightforward and daily phase, losing one's way may turn out to be an annoying experience, resulting in anxiety and nuisance. Negative consequences like these caused by direction loss have turned the concept of wayfinding to a non-negligible criterion in design. This text aims at meeting designers with the concept, bringing its significance forward and raising awareness as well. At the same time, it is a theoretical compilation for future research. Observing the city, the individual can perceive the environmental elements and communicate with the whole while (s)he is in motion. The substantiality of movement, i.e. wayfinding in space in accordance with a purpose comes on the scene at this point. During the period of wayfinding, cognitive maps that enable the movements of individuals within the environment are used. Therefore, convenience of the formation of the cognitive map and its completeness affect the wayfinding behavior in an environment. Visual access to spatial clues, architectural differences, usage of signage and spatial configurations are considered to be the variables that influence the wayfinding experience. The feasibility of direction finding of a built environment is an outstanding architectural criterion for both users and perception of service and brand identity in that environment. Consequently, that designers and urban planners focus on the concept at the intellectual phase of design has importance in designing environments with feasible wayfinding.
Keywords: Spatial cognition; locomotion; spatial orientation; navigation; wayfinding; wayfinding and legibility; SPATIAL KNOWLEDGE; MAPS; Architecture